STRATEGI PENINGKATAN WIRAUSAHA UNTUK MENINGKATKAN DAYA JUAL USAHA DI UPPKA LUMINTU I BINTARAN - Warsihapsari, Tri; Yuwati, Herina (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2025)
This research is about Entrepreneurial Enhancement Strategy for Business Selling Power in UPPKA Lumintu Bintaran. This is very important to do because if observed UPPKA Lumintu 1 Bintaran is more advanced compared to other UPPKA. Researchers want to know how to advance the business so that it remains advanced as it is today. This research will use sources from UPKKA and its members. The research was conducted using a qualitative descriptive method in order to reveal complete data. The output of this research is expected to add to the thinking of the treasury of science, especially to develop UPKKA. In addition, the expected practical benefits can contribute to the community's thinking to find out the existing problems and how to develop them so that the programs implemented will be right on target.